Answer:
1/4
Step-by-step explanation:
To find the average rate of change we find
f(3) -f(0)
----------
3-0
We need to find f(3) = 1/4 (3)^2 -4 = 1/4 (9) -4 = 9/4 -4 = -7/4
f(0) = 1/4 (0)^2 - 4 = -4
f(3) -f(0)
----------
3-0
-7/4 - (-4)
---------------
3-0
-7/4 +4
-----------
3-0
-7/4 +4
-----------
3-0
-7/4 +16/4
----------------
3
9/4
---------
3
9/12
1/4
Answer:
3/4
Step-by-step explanation:
The x values are 0 and 3. Use the formula y2-y1/x2-x1
Plug in the x factors into the orginal equation. Should look like the equations below:
f(x)=1/4(0)^2-4 -------> -4
f(x)=1/4(3)^2-4 --------> -7/4Now plug it in to the formula we saved earlier.
-7/4-(-4)/3-0= -7/4+4/3= -7/4+16/4/3
Then simplify it.
9/4/3, and in this case we have a fraction in a fraction and when this happens just multiply the equation by the x variables reciprical which in this case the x is 3 so the equation is multiplied by 1/3 and you would get 9/12. Now simplify that and you get 3/4.
(x+y=21
2x = 33+ y
Answer:
(18, 3 )
Step-by-step explanation:
Given the 2 equations
x + y = 21 → (1)
2x = 33 + y → (2)
Rearrange (2) expressing y in terms of x by subtracting 33 from both sides
y = 2x - 33 → (3)
Substitute y = 2x - 33 into (1)
x + 2x - 33 = 21, that is
3x - 33 = 21 ( add 33 to both sides )
3x = 54 ( divide both sides by 3 )
x = 18
Substitute x = 18 into (3) for corresponding value of y
y = (2 × 18) - 33 = 36 - 33 = 3
Solution is (18, 3 )
Answer:
Step-by-step explanation:
x+y = 21 —> (A)
2x = 33 + y — (B)
Form eq B
2x = 33 + y
Or y = 2x - 33
By putting the value of y in equation A
x + 2x -33 = 21
3x = 21 + 33
3x = 54
x = 54/3
x = 18
Now,
y = 2 (18) -33
= 36 - 33
= 3
Thus, s.s ={( 18,3)}